Respuesta :

Step-by-step explanation:

  • Just apply the quadratic formula [tex]x=\frac{-b \left \ {{+} \atop {-}} \right. \sqrt{b^{2}-4ac} }{2a}[/tex]
  • Your equation is [tex]4x^2-6x+1[/tex]
  • Every quadratic equation follows the general form [tex]ax^2+bx+c[/tex]
  • In this case [tex]a=4,b=-6,c=1[/tex]
  • Substitute into the quadratic formula:
  • [tex]x=\frac{-(-6) \left \ {{+} \atop {-}} \right. \sqrt{(-6)^{2}-4(4)(1)} }{2(4)}\\x=\frac{6 \left \ {{+} \atop {-}} \right. \sqrt{36-16} }{8}\\x=\frac{6 \left \ {{+} \atop {-}} \right. \sqrt{20} }{8}[/tex] Now take note that the square root of any number gives a (+) and (-) result, so two different answers
  • [tex]x=\frac{6 + \sqrt{20} }{8} ,and\\x=\frac{6 - \sqrt{20} }{8}[/tex] are the answers